Theft Is Property! Dispossession and Critical Theory - Nichols, Robert (Duke University Press, 2020)
Drawing on Indigenous peoples' struggles against settler colonialism, Theft Is Property! reconstructs the concept of dispossession as a means of explaining how shifting configurations of law, property, race, and rights have functioned as modes of governance, both historically and in the present. Through close analysis of arguments by Indigenous scholars and activists from the nineteenth century to the present, Robert Nichols argues that dispossession has come to name a unique recursive process whereby systematic theft is the mechanism by which property relations are generated. In so doing, Nichols also brings long-standing debates in anarchist, Black radical, feminist, Marxist, and postcolonial thought into direct conversation with the frequently overlooked intellectual contributions of Indigenous peoples.